Quantitative Contrast-Enhanced Ultrasound of Intraplaque Neovascularization in Patients with Carotid Atherosclerosis - van den Oord, S. C. H.; Akkus, Z.; Bosch, J. G.; Hoogi, A.; ten Kate, G. L.; Renaud, G.; Sijbrands, E. J. G.; Verhagen, H. J.; van der Lugt, A.; Adam, D.; de Jong, N.; van der Steen, A. F. W.; Schinkel, A. F. L. (Ultraschall in der Medizin - European Journal of Ultrasound, 2015)
Purpose: Intraplaque neovascularization (IPN) is an increasingly studied marker of the vulnerable atherosclerotic plaque, and contrast-enhanced ultrasound (CEUS) is an in vivo imaging technique for the assessment of IPN. The purpose of this study was to test novel quantification methods for the detection of carotid IPN using CEUS.Materials and Methods: 25 patients with established carotid atherosclerosis underwent bilateral carotid CEUS using a Philips iU-22 ultrasound system with an L9 – 3 transducer. Visual scoring of IPN was performed using a 3-point score. Quantification of IPN was performed using novel custom developed software. In short, regions of interest were drawn over the atherosclerotic plaques. After motion compensation, several IPN features were calculated. Statistical analysis was performed using Spearman’s rho. Reproducibility of the quantification features was calculated using intra-class correlation coefficients and mean differences between calculations.Results: 45 carotid arteries were available for the quantification of IPN. The quantification of IPN was feasible in all 45 carotid plaques. The IPN area, IPN area ratio and neovessel count had a good correlation with the visual IPN score (respectively ρ = 0.719, ρ = 0.538, ρ = 0.474 all p < 0.01). The intra-observer and inter-observer agreement was good to excellent (p < 0.01). The intra-observer and inter-observer variability was low.Conclusion: The quantification of carotid IPN on CEUS is feasible and provides multiple features on carotid IPN. Accurate quantitative assessment of IPN may be important to recognize and to monitor changes during therapy in vulnerable atherosclerotic plaques.
Keywords: carotid arteries; ultrasound; angiogenesis; arteriosclerosis; contrast agents